Pengaruh Model Problem Based Learning (PBL) Terhadap Hasil Belajar Siswa Kelas V pada Tema 5 Subtema 3 SDN 095552 Jln. Asahan - Janmariando Pangaribuan; Rio Parsaoran Napitupulu; Radode K. Simarmata (Journal on Education, 2023)
The selection of learning models is very influential on the learning outcomes obtained by students. This study aims to determine the effect of the Problem Based Learning model on the learning outcomes of fifth grade students in theme 5 (Ecosystem) sub-theme 3 (Ecosystem Balance) learning 5&6. This study used a pre-experimental study using the One Group Design Pretest-Posttest design. This research was conducted for 2 weeks starting from March 29 to April 12 2023, with a total sample of 28 students consisting of 13 female samples and 15 male samples. Based on the results of the data analysis test carried out, the results of the Hypothesis Test were obtained from the results of the tests given to students, so that tcount = 13,072 and ttable = 2,056 with tcount > ttable = 13,072 > 2,056 then H0 was rejected and Ha was accepted. With this explanation it can be concluded that there is an influence of the Problem Based Learning model on student learning outcomes in theme 5 sub-theme 3 learning 5&6 in class V SD Negeri 099952 JLN. Sharpen